2016
DOI: 10.1007/s00795-016-0142-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of intratumoral lymphatic microvessel density, vascular endothelial growth factor C and cell proliferation in salivary gland tumors

Abstract: Lymphatic dissemination is one of the most important pathways for metastasis in many solid tumors, including head and neck carcinomas. The lymphatic growth of cancer has been used as a significant independent adverse prognostic factor and provides information about tumor progression. Salivary gland tumors present different prognoses and have the ability to develop metastases; however, this information regarding the lymphatic spread is scarce. This paper quantifies the lymphatic microvessel density (LMD) in ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…These findings were consistent with Gleber-Netto et al [38], who reported cytoplasmic reaction in the neoplastic cells and at the periphery of the tumour nests of mucoepidermoid carcinoma cases. Also, Americo et al [39] stated that podoplanin was used to stain the cytoplasm and cytoplasmatic membrane of lymphatic endothelial cells in mucoepidermoid carcinoma. Dezfuli et al [40] recorded a cytoplasmic reaction in the tumour cells of mucoepidermoid carcinoma cases in their study.…”
Section: Low Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with Gleber-Netto et al [38], who reported cytoplasmic reaction in the neoplastic cells and at the periphery of the tumour nests of mucoepidermoid carcinoma cases. Also, Americo et al [39] stated that podoplanin was used to stain the cytoplasm and cytoplasmatic membrane of lymphatic endothelial cells in mucoepidermoid carcinoma. Dezfuli et al [40] recorded a cytoplasmic reaction in the tumour cells of mucoepidermoid carcinoma cases in their study.…”
Section: Low Expressionmentioning
confidence: 99%
“…Many studies have reported the role of lymphangiogenesis in the progression of this lesion. However, the association between lymphatic micro vessel density and lymph node metastasis in SGCs is unclear, and information regarding the lymphatic spread is scarce [6].…”
Section: Introductionmentioning
confidence: 99%